Keadilan Gender dalam Pendidikan Islam di Pondok Pesantren - Sumaryati Sumaryati (Tarbawiyah Jurnal Ilmiah Pendidikan, 2018)
This paper describes gender justice in Islamic education in Islamic boarding schools that has not been done optimally. This is due to cultural constraints which have resulted in a less gender responsive policy, namely the patriarchal system. In the patriarchal system men control women's work. The implication is that santri occupy the main authority in the pesantren environment. In analyzing the nature and culture theory, women and their functions are identified with "life", placing themselves close to nature. While men are placed as a group entitled to fill the public sector. In boarding schools, generally still treat santri with the dichotomy of the role. As a result santri have limited access to activities outside the pesantren. Subordination to students is also evident from the lack of opportunities to appear in public. Because something that is mass and prestigious is considered a male area. Finally, the experience gained by the santriwan was greater. The impact of the provision received by students for preparation for plunge in the community is not as big as santriwan.